KEWENANGAN PENGADILAN AGAMA DALAM PENYELESAIAN SENGKETA PERBANKAN SYARIAH - A.A. OKA DHERMAWAN (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2012)
The authority of Religion Court in resolving the Shariah Banking disputes regulated in article 55, verse (1) of Sharia Banking Regulation. There are two types of dispute resolution methods, namely non litigation (out of court) and litigation (through the court). The resolution procedure using non litigation method basically uses the agreement from all parties. If the resolution is made through arbitrate institution, the procedure of the dispute resolution is regulated in Regulation No. 30 the year of 1999, about Arbitration and the Alternative of Dispute Resolution. The procedure of the resolution of the Shariah banking dispute which proposed by the law abider, an Islamic person or legal institution and/ or they who abide the Islamic law can be done in two ways. First is special judicial procedure when the case is dismissed, canceled and verstek by the verdict of dismissal, cancelation and verstek. When the case is dismissed, and canceled, there will not be any legal action, but the related parties can reapply the case. When the case is on verstek verdict, the legal action will be in the form of verzet. The second is the regular case, it is applied when all the trial procedures are fulfilled perfectly and the granted or denied with appeal as the law action.